Convective Heat And Mass Transfer - Kays, W. M.; Crawford, Michael; Weigand, Bernhard (TamilNadu: Mcgraw Hill, 2018)
Key Features Numerous design sections show how analytical techniques are actually used to model heat exchangers, etc. Computer Problems are included in each chapter problem set. About the Book: Convective Heat and Mass Transfer Convective Heat and Mass Transfer presents a strong theoretical basis for the subject, concentrating on boundary layer theory, with special emphasis on laminar and turbulent thermal boundary layers.
Contents Chapter 1: Introduction Chapter 2: Conservation Principles Chapter 3: Fluid Stresses and Flux Laws Chapter 4: Differential Equations for the Laminar Boundary Layer Chapter 5: Integral Equations for the Boundary Layer Chapter 6: Differential Equations for the Turbulent Boundary Layer Chapter 7: Laminar Internal Flows: Momentum Transfer Chapter 8: Laminar Internal Flows: Heat Transfer Chapter 9: Laminar External Boundary Layers: Momentum Transfer Chapter 10: Laminar External Boundary Layers: Heat Transfer Chapter 11: Turbulent External Boundary Layers: Momentum Transfer Chatper 12: Tubulent External Boundary Layerss: Heat Transfer Chapter 13: Turbulent Internal Flows: Momentum Transfer Chapter 14: Turbulent Internal Flows: Heat Transfer Chapter 15: Influence of Temperature-Dependent Fluid Properties Chapter 16: ConvectiveHeat Transfer at High Velocities Chapter 17: Convective Heat Transfer with Body Forces Chapter 18: Convective Mass Transfer: Basic Definitions and Formulation of a Simplified Theory Chapter 19: Convective Mass Transfer: Evaluation of the Mass-Transfer Conductance from the Conserved-Property (P) Equation Chapter 20: Convective Mass Transfer: Examples for Application of the Simplified Method